2021
DOI: 10.1039/d1ay01682b
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electrochemical sensing of heavy metal ions based on a g-C3N4/CNT/NH2-MIL-88(Fe) nanocomposite

Abstract: Porous composite g-C3N4/CNT/NH2-MIL-88(Fe) is rich in N-containing function groups, and can be used to simultaneously detect Cd2+, Pb2+, Cu2+ and Hg2+ in water via square wave stripping voltammetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Few studies reported on the use of newly synthesized MOFs and COFs as sole electrode modifiers. 284,288,291,302 Zeolitic imidazolate frameworks (ZIFs), 154,177,201,236,279,284,286 amino-functionalized Zr-based MOFs (Universitet i Oslo (UiO) type, i.e., NH 2 -UiO-66), 42,53,151,152,209,216,283,285 and Materials of Institute Lavoisier (MILs), 164,212,295 are among the main types of MOFs used as electrode modifiers. The presence of amino groups or imidazole in MOFs facilitates the formation of coordination bonds with heavy metals, improving the adsorption ability of the analytes and thus improving the analytical performance of the electrodes.…”
Section: Metal-and Covalent-organic Framework As Electrode Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies reported on the use of newly synthesized MOFs and COFs as sole electrode modifiers. 284,288,291,302 Zeolitic imidazolate frameworks (ZIFs), 154,177,201,236,279,284,286 amino-functionalized Zr-based MOFs (Universitet i Oslo (UiO) type, i.e., NH 2 -UiO-66), 42,53,151,152,209,216,283,285 and Materials of Institute Lavoisier (MILs), 164,212,295 are among the main types of MOFs used as electrode modifiers. The presence of amino groups or imidazole in MOFs facilitates the formation of coordination bonds with heavy metals, improving the adsorption ability of the analytes and thus improving the analytical performance of the electrodes.…”
Section: Metal-and Covalent-organic Framework As Electrode Modifiersmentioning
confidence: 99%
“…Five main types of NMs, i.e. , graphene, graphene oxide (GO) and reduced graphene oxide (rGO), 22–92 NPs, 23–25,27,31,56,57,59,64,67,70,83,86,87,93–138 single and multiwalled carbon nanotubes (SWCNTs and MWCNTs), 32,83,89,98,99,101,113,129,133,139–162 nanosheets, 34,85,107,111,139,162–166 and nanofibers, 167–169 have been employed in the modification of the electrodes used in the determination of heavy metals. Nanocubes, nanoflakes, nanospheres, and nanodiamonds 75,170–175 are among the other types of NMs used in the modification of the electrodes.…”
Section: Nanomaterials As Electrode Modifiersmentioning
confidence: 99%
“…The successful fabrication of NH 2 -MIL-88(Fe) (500 nm) nanoparticles embedded on the sheet structure of g-C 3 N 4 and the tubular structured H-CNTs was confirmed by the decrease in peak current and most significant impedance R ct value. 92 Under optimal conditions, g-C 3 N 4 /CNT/NH 2 -MIL-88(Fe)/GCE with an effective surface area of 0.04645 cm 2 was employed to simultaneously detect Cu 2+ , Cd 2+ , Pb 2+ , and Hg 2+ via SWSV in (ABS) 0.2 M Acetate buffer solution (pH 5.4). The enhanced SWSV signal observed in g-C 3 N 4 /CNT/NH 2 -MIL-88(Fe) is due to g-C 3 N 4 doped in MOFs composite that significantly improved response towards the HMIs along with tri-s-triazine units and a substantial number of hydrophilic terminals, -NH-and -NH 2 groups.…”
Section: Application Of Mofs Composites In Hmis Sensingmentioning
confidence: 99%
“…The MIL-101 (Cr) MOF-based electrochemical determination of Cd 2+ has been proposed by employing SWASV . Recently, a nanocomposite of NH 2 -MIL-88­(Fe) with carbon nanotubes and graphitic carbon nitride (g-C 3 N 4 /CNT/NH 2 -MIL-88­(Fe)) was used for the detection of nanomolar concentrations of Cd 2+ . In all the above studies, the limit of detection (LOD) of the sensor was limited to 0.04–0.2 μM.…”
Section: Introductionmentioning
confidence: 99%